2009
DOI: 10.1007/s00419-009-0349-3
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis of a functional graded material plate with a circular hole

Abstract: This paper is to study the two-dimensional stress distribution of a functional graded material plate (FGMP) with a circular hole under arbitrary constant loads. With using the method of piece-wise homogeneous layers, the stress distribution of the functional graded material plate having radial arbitrary elastic properties is derived based on the theory of the complex variable functions. As examples, numerical results are presented for the FGMPs having given radial Young's modulus or Poisson's ratio. It is show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 26 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…113.463 (3) 91.928 (2) 91.928 (2) 77.619 (2) 38.688 (2) 38.688 (2) 34.955 (1) 34.955 (1) 22.309 (1) The superscript numbers within the parenthesis indicate the mode of buckling…”
Section: Effect Of Foundation Stiffness Coefficients On Critical Buckmentioning
confidence: 99%
See 2 more Smart Citations
“…113.463 (3) 91.928 (2) 91.928 (2) 77.619 (2) 38.688 (2) 38.688 (2) 34.955 (1) 34.955 (1) 22.309 (1) The superscript numbers within the parenthesis indicate the mode of buckling…”
Section: Effect Of Foundation Stiffness Coefficients On Critical Buckmentioning
confidence: 99%
“…(22) and the quadratic function form of in-plane loading into the stability Eq. (21) and applying the kinematic and constitutive relations, leads to the buckling equation as…”
Section: In-plane Loading Configurationmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the material inhomogeneity on the stress concentration for FGM has attracted many researchers in the multidiscipline area of materials, machines, mechanics and applied mathematics. Based on the theory of complex variable functions, two-dimensional stress distribution of an FGM plate with a circular hole under arbitrary constant loads was derived by Yang et al [6]. Dineva et al [7] addressed the evaluation of the stress and electric field concentrations around a circular hole in a FGM piezoelectric plane subjected to anti-plane elastic SH-wave and in-plane time-harmonic electric load.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the stress concentration factor is reduced when Young's modulus progressively decreases towards the hole. Subsequently, Yang et al (2009) investigated the stress field around a circular hole in a FGM plate. They used piece-wise homogeneous layers and complex variable methods.…”
Section: Introductionmentioning
confidence: 99%